In Vitro Characterization of Poly-Glycolyc Lactic-Co Acid (PLGA) –Collagen Based on Red Snapper Fish Scales (Lutjanus Sp.) Coating Chitosan as Duramater Artificial Candidate - Jabbar, Hajria; Widiyanti, Prihartini; Paramadini, Adanti Wido; Putri, Dina Kartika; Isfandiary, Andini (Folia Medica Indonesiana, 2020)
Head trauma was the third cause of deaths that have a high rank that can make serious head injury for 25.5%-54.9%. This study has been conducted by making a replacement layer of the brain (dura) to overcome the impact of dural defect by utilizing waste fish scales red snapper (Lutjanus sp.). Synthesis brain membranes lining processed by casting method with each various concentrations of chitosan coating of 1%, 1.5%, and 2% then dried using vacuum dry. The samples then were characterized by tensile test, FTIR, SEM and MTT Assay. FTIR test results showed that red snipperscales can produce collagen powder at amide A group with stretching of –NH functional group, amide B group has stretching of CH2 assymetry, amide I area, amide II and amide III area which show –NH bonding. Tensile test results showed that the combination between PLGA-Collagen Chitosan Coating 2% produced the highest tensile strength is 4.8 MPa which meet the standards of human duramater strength. MTT Assay results showed that the dural membrane produced no toxic seen from living cells reached 98.32%. Poly - Glycolyc Lactic - Co Acid (PLGA) - collagen coating chitosan based on red snapper fish scales (Lutjanus sp.) composites has potency as duramater artificial candidate due to the chemistry, biological and physical characteristics.